Avanços e desafios na implementação da autogestão em empreendimentos solidários fomentados por políticas públicas municipais em São Carlos/SP - Fajardo, Rita de Cássia Arruda (2014)
This thesis, aims to identify changing and excluding elements in the solidarity economy management process, together with a group of workers of solidarity economic enterprises, promoted by the local public policy of solidarity economy, seeking ways to improve the daily practice of management. An introduction with the contextualization of the theme, a literature review on self-management in solidarity economy groups and a characterization of the public policy of solidarity economy, focused in São Carlos/SP, were performed. The methodology used for conducting the present research was the Critical Communicative Methodology (CCM), which places the dialogue, interaction, interpretation and validation of the results collectively, in a communicative process of knowledge production. The CCM provides, through communication, the construction of a critical analysis of reality by the people who experience it, seeking, thereby, to obtain results to transform or validate a social reality. It is a participatory methodology, which enables in its development the flattening of the relations between participants/researcher through consensus building. Data collection in the CCM is performed using quantitative and qualitative methods, as in a traditional methodology. What makes this methodology different is its participatory nature, in which the representatives of communities or collectives that are part of the research participate of the project, investigation process and its conclusions, in order to interact, reflect and make decisions in all these steps, following the communicative orientation's postulates. To carry out the research, a critical communicative group with people from solidarity economic enterprises, participants of São Carlos public policy, was formed. Analysis matrices were produced, so that the excluding or changing elements identified by the group were distributed into two categories: public policy and solidarity economy. After the realization of communicative groups, the systematization of data was performed by the researcher and the results submitted to the group for discussion, construction and validation of its final content. The matrices with the final result listed 70 elements, 46 (65.7%) classified as excluding dimension and 24 (34.3%) in the changing dimension. It means that the dialogue pointed out that the themes solidarity economy and public policy have more challenges to be overcome than elements that have been changing the reality of enterprises fostered by São Carlos public policy. This research considers that these changing elements identified should be strengthened. For those elements identified as excluding, they represent a platform that can guide new actions or even redirect those ones that already exist, so they can become changing in public policy and in the self-management experience.